A to Z Textile Mills Ltd., invests in manufacturing and distributing Aflasafe biocontrol products in Tanzania - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, IITA signed a Technology Transfer and Licensing Agreement with A to Z Textile Mills, Ltd. The agreement established a plan for local manufacture, distribution, and sale of Aflasafe TZ01 in Tanzania. This follows IITA’s three-phase approach to develop a country-specific commercialization strategy, select investors, and execute a business plan. Availability of Aflasafe at scale allows farmers to produce crops complying with aflatoxin standards furthering trade opportunities and income generation for themselves and protecting consumers’ nutrition and health.